THE ROLE OF COMMITMENT IN EMPLOYEE ENGAGEMENT WITH PERFORMANCE: LITERATURE REVIEW - Titiek Ambarwati; Sopiah (International Journal Labs, 2022)
Commitment is an organizational approach intended to assure that employees are dedicated to organizational goals and principles, urged to help the organization succeed, and at the same time able to increase their own sense of security. Employee engagement plays a very important role in any organization because it is connected to the output of commitment and performance. When a sufficient number of people care about doing a good job and about the organization's work, engagement happens. The primary goal of the research was to present the researchers' opinions about the connection between employee engagement and organizational performance along with gaps that allow scope for future research